2003
DOI: 10.3109/10929080309146058
|View full text |Cite
|
Sign up to set email alerts
|

Vessel-Based Non-Rigid Registration of MR/CT and 3D Ultrasound for Navigation in Liver Surgery

Abstract: The proposed registration method is fast enough for clinical application in liver surgery. Initial accuracy results are promising and must be further evaluated, particularly in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 21 publications
2
37
0
2
Order By: Relevance
“…VOLUSON) but these are far more expensive. Tracked US has previously (Peterhans 2010, Lange 2003) been used as a tool for liver surgery navigation due to its ability to resolve blood vessels and some types of tumors. This technique is used in both open and laparoscopic cases.…”
Section: Intraoperative Usmentioning
confidence: 99%
See 1 more Smart Citation
“…VOLUSON) but these are far more expensive. Tracked US has previously (Peterhans 2010, Lange 2003) been used as a tool for liver surgery navigation due to its ability to resolve blood vessels and some types of tumors. This technique is used in both open and laparoscopic cases.…”
Section: Intraoperative Usmentioning
confidence: 99%
“…The results of these studies suggest that there can be improvements to registration by accounting for nonrigid deformations. Lange (2003) published a study on using b-splines to deform and match preoperative segmented blood vessels to match intraoperative US detected vessels. Their algorithm was able to match about 30 vessel segments with only 1-2 mismatches per patient.…”
Section: Liver Deformation Registrationmentioning
confidence: 99%
“…11 However, in addition to the challenge of accurately determining the boundary conditions for the complex shape of the organs and/or complex interaction forces between the region of interest (ROI) and surrounding tissues, which is required by FEM, FEM suffers from the problem of slow convergence. In the case of liver surgery, Lange et al 12 reported that registration accuracy in the range of 3 mm with a manual interaction time of about 10 min is reasonable for clinical application. During radiotherapy treatment, it is highly desirable to achieve an image registration accuracy of better than 3 mm at the treatment target.…”
Section: Introductionmentioning
confidence: 99%
“…3 Since these methods use freehand US and assume a large coverage of the liver, they can not be applied in laparoscopy given the restricted probe movement and field of view. As an alternative to freehand US, other authors register 3D US, either by using reconstructed vessels as features 4,5 or by using segmented liver surface and vessels. Figure 1.…”
Section: Introductionmentioning
confidence: 99%